Serial return and regional working-class self-expression: a cultural history of the East Midlands - Wakefield, Thirza (2021)
My research focuses on representations of working-class life in the East Midlands. It offers for the first time a comparison of literary and audiovisual works by East Midlands-born and based artists, among them the largely underexplored early dramas of D. H. Lawrence, and Shane Meadows’s This is England television series, which has yet to be subjected to sustained critical analysis. I draw on recent developments in regional studies, neo-genetic criticism, post-colonialism, town planning studies, and cultural sociology, as well as conceptualisations of place and space and person-place relationships that have dominated the discipline of geography since the 1970s, to prove that Lawrence’s mining plays, Meadows’s This is England sequence, and Alan Sillitoe’s four-book Seaton novel series mobilise similar formal and aesthetic strategies for the representation of regional ways of life, and share a basis in the eschewal of the singular, the fixed, and the finished. By examining these works of drama, literary fiction, and television side-by-side, I show that these three artists have in common an artistic sensibility arising from a responsiveness to place, social class, and cultural marginality. My thesis charts a cultural lineage of the East Midlands region, and argues that serialness and its correlatives, repetition and open-endedness, are modes of expression typical of the representation of working-class identity in this historically under-regarded part of the country.